Of Microscopes and Meeting Places: A Literature Review Examining Barriers to Indigenous Participation in STEM - Madeline Bollinger; Brian M. McSkimming (MDPI AG, 2024)
STEM (Science, Technology, Engineering, and Mathematics) was once not seen as a place for everyone. In fact, a powerful majority of people believed that individuals had to have predetermined characteristics that made them able to bear such vast and liberating knowledge. Centuries later, concentrated efforts are still needed to reverse the damage that the prevalence of such an ideology caused. When one considers the exclusion of individuals from a particular field, they may only see one side of the story; they may think that the only factor stopping the out-group from participating is the in-group trying to keep them out. The bigger picture tells the story of the consequences of enduring exclusion of the out-group, even well after explicit exclusionary tactics cease to exist. The awareness and study of this phenomenon in regard to several groups of historically excluded people have expanded in the modern era, helping to reduce its lasting effects. Some groups continue to participate in STEM at a much lower rate than their peers. Native Americans are a particularly interesting example of this. This review will explore some of the various reasons posed for the way and rate at which Native Americans are involved in STEM education and will attempt to determine the prevalence of each explanation and their interactions with each other.